Achieving high efficiency Cu2ZnSn(S, Se)4 solar cells by non-toxic aqueous ink: Defect analysis and electrical modeling. (August 2016) - Wei, Shih-Yuan; Liao, Yueh-Chun; Hsu, Chia-Hao; Cai, Chung-Hao; Huang, Wei-Chih; Huang, Mao-Cheng; Lai, Chih-Huang
Abstract: An extremely environment-friendly aqueous-ink process for Cu2 ZnSn(S, Se)4 (CZTSSe) fabrication is reported. The aqueous ink is composed of SnSX nanoparticles, zinc ions from zinc nitrate (Zn(NO3 )2 ), and metal complex made of copper nitrate (Cu(NO3 )2 ) and thioacetamide (C2 H5 NS). The combinations of negatively surface-charged SnSX nanoparticles and cations form electric double layers and lead to a well-mixed and dispersed aqueous CZTSSe precursor ink, which eliminates the usage of hazard solvent. The results of X-ray diffraction, Raman spectroscopy, scanning electron microscope, and auger electron spectroscopy show that the CZTSSe film possesses a single phase, good crystallinity, and uniform composition after an annealing process. A high cell efficiency of 10.05% is achieved by using this novel aqueous-ink approach. To further investigate the possible root cause of efficiency limitation, the electrical properties of CZTSSe cells are studied. The existence of deep donor defects, which results in low carrier concentration as well as collapsed short-circuit current and fill factor at low temperature, is proposed. Our proposed model suggests that the relatively deep p-type defects (CuZn ) as the major carrier source, the existence of deep n-type defects and short diffusion length are the key limitations for achieving high efficiency of CZTSSe solar cells. Graphical abstract: An environment-friendly aqueous-ink process for Cu2 ZnSn(S, Se)4 fabrication, based on the idea of electric double layers, yields a high PCE of 10.05%. The importance of defects on electrical properties and the key limitations for achieving high efficiency of CZTSSe solar cells are proposed. Highlights: A novel aqueous-ink process for CZTSSe fabrication is developed. A high cell efficiency of 10.05% is achieved by using this novel approach. The existance of deep n-type defect is proposed. Electrical model explaining the specific electrical properties in CZTSSe is proposed. Guidelines for improving the cell efficiency are suggested based on simulation.